Pengaruh disiplin kerja dan lingkungan kerja terhadap kinerja karyawan bagian produksi PT. Nafal Tiara Abadi Pekanbaru - Liawandy, Feru; Indarti, Sri; ', Marzolina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The research was conducted at PT. Nafal Tiara Abadi Pekanbaru, with theaim to determine the effect of work discipline and work environment eithersimultaneously or partially on the performance of the production employee at PT. Nafal Tiara Abadi Pekanbaru. The population in this study were all employees at PT. Nafal Tiara Abadi Pekanbaru totaling 42 people, and overall the employees sampled by census method. The method of data analysis used in this research is descriptive quantitative method and multiple linear regression analysis using SPSS version 18.0. The result showed that the work discipline and work environment simultaneously have a significant effect on employee performance. The magnitude of the effect that (R2) by the two independent variables together against the dependent variable 70,4%, while the remaining 29,6% is influenced by other variables not examined in this study. The results of the partial regression test (t test) showed that the work discipline and work environment has a partially significant effect on employee performance. As for the recommendation that the authors propose that need to be done at regular training to employees so that employees are able to operate the device properly, always pay attention to employee attendance and create a conducive working environment.Keywords : Work Discipline, Work Environment, and Employee Performance